Transnational corporations: Impediments or catalysts of social development? - Eric Kolodner (United Nations Research Institute for Social Development (UNRISD), 1994)
This paper examines the relationship between TNCs and social development with respect to their effects on employment, consumer safety and health, the environment and transfer of technology. Furthermore, it discusses the current expansion in corporate rights and suggests some methods by which governments and NGOs can foster corporate social responsibility. Finally, it argues that, as prevailing ideologies shift and transnational corporations extend their global reach, the international community must ensure that the extraordinary economic and political power of these entities is harnessed to the goals of social development.
Keywords: 330